2021
DOI: 10.1007/s10654-021-00803-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and risk of cardiovascular disease in men and women: the HUNT study

Abstract: The association between bone mineral density (BMD) and cardiovascular disease (CVD) is not fully understood. We evaluated BMD as a risk factor for cardiovascular disease and specifically atrial fibrillation (AF), acute myocardial infarction (AMI), ischemic (IS) and hemorrhagic stroke (HS) and heart failure (HF) in men and women. This prospective population cohort utilized data on 22 857 adults from the second and third surveys of the HUNT Study in Norway free from CVD at baseline. BMD was measured using single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…Higher eBMD was more protective against incident CVDs in women compared to men, particularly for IHD, HF, and arrhythmia. This is in contrast to the HUNT study, 30 which showed a small protective association of BMD on MI and AF in men but not in the female population. Conversely, the research conducted by Yang et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher eBMD was more protective against incident CVDs in women compared to men, particularly for IHD, HF, and arrhythmia. This is in contrast to the HUNT study, 30 which showed a small protective association of BMD on MI and AF in men but not in the female population. Conversely, the research conducted by Yang et al.…”
Section: Discussioncontrasting
confidence: 99%
“…More recently, the HUNT study did not find an association between forearm BMD and new-onset HF in European men or women, although ascertainment of HF cases based on diagnostic coding was not validated, and events in men were relatively modest in number. 27 The present investigation in Health ABC, which includes >4-fold Black individuals as the prior CHS report, newly reveals an inverse association between areal BMD of the hip, as well as volumetric BMD of the spine, and incident HF in Black women. The current analysis also confirms the positive relationship between hip BMD and new-onset HF in Black men observed in CHS.…”
Section: Prior Studiesmentioning
confidence: 52%
“…Our prior work in CHS 17 evaluated BMD of the hip, detecting effect modification by both sex and race: a significant association was observed in male but not female participants, wherein lower BMD was associated with higher incidence of HF in White men, but lower incidence of HF in Black men. More recently, the HUNT study did not find an association between forearm BMD and new‐onset HF in European men or women, although ascertainment of HF cases based on diagnostic coding was not validated, and events in men were relatively modest in number 27 …”
Section: Discussionmentioning
confidence: 99%
“…As prevalent public health issues with widespread impact and significant consequences, OP and CVD have consistently garnered considerable attention. While numerous prior epidemiological studies have reported the connection between these conditions, the precise association remains elusive (34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Several factors may contribute to this ambiguity.…”
Section: Discussionmentioning
confidence: 99%